(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objectives: This study aimed to identify community-level environmental and behavioral determinants associated with acute pediatric diarrhea in three peri-urban coverage hospitals in Kathmandu. Methods: This cross-sectional community-based study was carried out in three peri-urban Kathmandu hospitals starting in May 2024 and recruited 550 children under five years of age presenting with diarrheal symptoms following guardian consent, utilizing semi-structured questionnaires for data collection. Results: Abdominal cramps (66.7%) and mucus in stool (64.2%) were the most prevalent symptoms whereas blood in stool (8.5%) and blood in urine (1.6%) were least common. Statistical analysis revealed that the predominant source of drinking water (Jar Water, 65.8%) was strongly associated with both vomiting and watery stool (both χ², p < 0.001). Multivariate logistic regression identified age (adjusted OR = 1.32, 95% CI = 1.15–1.52) and putting toys in the mouth (adjusted OR = 2.02, 95% CI = 1.29–3.15) as significant, independent predictors of fever (p ≤ .002). While the fever model showed 69.8% classification accuracy, its overall fit was borderline poor (Hosmer-Lemeshow p = 0.045). ROC analysis confirmed age as the best single predictor, while stool consistency and mucus in stool had poor individual discriminatory power. Conclusions: These findings underscore the necessity of targeted public health interventions focusing on child-specific hygiene practices and the safety of household drinking water sources in this rapidly urbanizing context.